The Influence of Work Discipline and Workload on Employee Performance with Organizational Commitment as a Mediating Variable in the Municipality of Pangkalpinang - Bangka - Farida Elmi; Lia Amalia; Setyo Riyanto; Novia Nila Sutarman; Novita (Baca Dulu Publisher, 2024)
This research is motivated by an agency that often only demands high performance from employees, without looking at the fundamental factors that influence performance, such as Discipline, Workload and Organizational Commitment. This type of research is quantitative research which aims to test hypotheses about the influence of independent variables on dependent variables in Pangkalpinang Municipality. The research uses SmartPLS 4 in processing data. From the results of this research, the author concludes that: (1)Work Discipline has a positive and significant effect on Organizational Commitment. (2)Workload has a negative and significant effect on Organizational Commitment. (3)Work Discipline has a positive and significant effect on Work Discipline. (4)Workload has a negative and significant effect on employee performance. (5)Organizational Commitment has a positive and significant effect on Employee Performance. (6)Work Discipline has a positive and significant effect on Employee Performance through Organizational Commitment. (7)Workload has a negative and significant effect on Employee Performance through Organizational Commitment.